High-yielding method for preparation of carbocyclic or N-containing heterocyclic β-keto esters using in situ activated sodium hydride in dimethyl sulphoxide. Issue 1 (2nd January 2016) - Popović-Djordjević, Jelena; Stepanović, Stepan; Došen-Mićović, Ljiljana; Ivanović, Evica; Ivanović, Milovan D.
ABSTRACT: It was found that NaH suspension in DMSO was highly activated when reacted with an alcohol. The in situ generated NaH/alkoxide mixture permitted very rapid and complete deprotonation and acylation of various cyclic ketones with alkyl carbonates at ambient temperature. Activated NaH/alkoxide in DMSO is particularly effective in Dieckmann condensations, where it affords 5- and 6-membered carbocyclic or N -containing heterocyclic β-keto esters in high yields. A heterocyclic Dieckmann condensation was performed on a molar scale, demonstrating the scalability of the procedure. Besides, DMSO is non-toxic, relatively inexpensive and environmentally benign solvent. GRAPHICAL ABSTRACT: